Trail guide to the body : - Biel, Andrew (Books Discovery, 2001)
Fascinating guide to locating bones, muscles, ligaments and more! 340 pages, 850 beautiful, hand-drawn illustrations. Over 350 unique palpation drawings Detailed palpatory instructions for: 100 bony landmarks 120 individual muscles 23 ligaments and other structures Over 100 side panels of anatomical curiosities and quirky insights Appendix listing synergist muscles.Easy-to-read pronounciation guides at the bottom of each page.Mr. Bones - that handy guide sharing advice and hints! Spiral-bound for easy, lay-flat usage. Durable semi-gloss paper.Attractive two-color format . Over 150,000 copies sold . Used in over 800 massage/bodywork schools in the US and Canada